The Glass Church: Robert H. Schuller, the Crystal Cathedral, and the Strain of Megachurch Ministry - Mulder, Mark T (Rutgers University Press, 2020)
Frontmatter -- Contents -- Preface -- Significant Dates for Robert Schuller and U.S. Politics, 1945–2015 -- 1. Constituency, Charisma, and Capital -- 2. The Imperative of Church Growth -- 3. Migrants to Orange County, California -- 4. The Possibility Thinker -- 5. No Hippies in the Sanctuary -- 6. Dig a Hole, Schuller -- 7. Always a New Project -- 8. When the Glass Breaks -- Coda. Ends and Beginnings -- Appendix: Research Methodology -- Notes -- Bibliography -- Index